Novel molecular determinants of viral susceptibility and resistance in the lipidome of Emiliania huxleyi. (23rd January 2014) - Fulton, James M.; Fredricks, Helen F.; Bidle, Kay D.; Vardi, Assaf; Kendrick, B. Jacob; DiTullio, Giacomo R.; Van Mooy, Benjamin A. S.
Summary Viruses play a key role in controlling the population dynamics of algae, including Emiliania huxleyi, a globally distributed haptophyte with calcite coccoliths that comprise ca. 50% of the sinking carbonate flux from the surface ocean. Emiliania huxleyi viruses (EhVs) routinely infect and terminate E. huxleyi blooms. EhVs are surrounded by a lipid envelope, which we found to be comprised largely of glycosphingolipids (GSLs) with lesser amounts of polar glycerolipids. Infection appears to involve membrane fusion between the virus and host, and we hypothesized that specific polar lipids may facilitate virus attachment. We identified three novel intact polar lipids in E. huxleyi strain CCMP 374 and EhV86, including a GSL with a monosaccharide sialic acid headgroup (sGSL); for all 11 E. huxleyi strains we tested, there was a direct relationship between sGSL content and sensitivity to infection by EhV1, EhV86 and EhV163. In mesocosms, the E. huxleyi population with greatest initial sGSL content had the highest rate of virus‐induced mortality. We propose potential physiological roles for sGSL that would be beneficial for growth but leave cells susceptible to infection, thus furthering the discussion of Red Queen‐based co‐evolution and the cost(s) of sensitivity and resistance in the dynamic E. huxleyi‐EhV system.